2000
DOI: 10.1002/hep.510310111
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of interferon treatment for advanced hepatocellular carcinoma

Abstract: The aim of this randomized controlled trial was to assess the efficacy of interferon alfa-2b (IFN) for the treatment of advanced hepatocellular carcinoma (HCC). Fifty-eight patients with HCC who were not suitable for resection, transplantation, ethanol injection, or arterial embolization were stratified according to their Okuda stage and randomized to receive IFN (3 ؋ 10 6 , 3 times a week, for 1 year) (n ‫؍‬ 30) or symptomatic treatment (n ‫؍‬ 28). Both groups were identical in terms of age, sex, performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
144
1
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(153 citation statements)
references
References 34 publications
0
144
1
8
Order By: Relevance
“…Several treatments of unresectable HCC, such as immunotherapy with interferon, 78,80 antiandrogen therapy, 65 internal radiation, 55 and arterial 47,52 or systemic chemotherapy, 74,76 have also been evaluated in comparison with conservative management. However, none included a sufficient number of patients to guarantee a robust analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several treatments of unresectable HCC, such as immunotherapy with interferon, 78,80 antiandrogen therapy, 65 internal radiation, 55 and arterial 47,52 or systemic chemotherapy, 74,76 have also been evaluated in comparison with conservative management. However, none included a sufficient number of patients to guarantee a robust analysis.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-a was the first cytokine to be used clinically in human cancers. It is of note that although the benefit derived from IFN-a on established HCCs remains rather disappointing (Llovet et al, 2000), several clinical studies have suggested that IFN-a might prevent HCC development in HBV-or HCV-related cirrhosis, although the data remain controversial and no clear mechanism has been described in these studies (Ikeda et al, 1998;Nishiguchi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, there were significant treatment-related toxicities in patients who received high-dose interferon. On the other hand, when a lower dosage (3 × 10 6 IU/m 2 , three times weekly) of interferon was used instead, there was no demonstrable clinical benefit [30] .…”
Section: Hormonal Therapymentioning
confidence: 99%